The Mediating Role of Trust and Commitment in the Relationship Between Service Quality and Member Loyalty in Women’s Cooperatives in Jember Regency - Fristyana Annuru Putri; Bambang Irawan; Mochammad Farid (Harmony Management: International Journal of Management Science and Business, 2025)
This study investigates the influence of service quality, trust, and commitment on member loyalty in Women’s Cooperatives in Jember Regency, Indonesia. Amid increasing competition from financial institutions and a declining number of active cooperatives, member loyalty has become a critical factor for sustainability. Drawing upon the Key Mediating Variable (KMV) model and relationship marketing theory, this research highlights how service quality and trust shape long-term cooperative-member relationships. The study also explores the unique role of commitment in fostering member retention in a cooperative context driven by social empowerment and collective welfare. Findings from previous literature underscore the positive and significant effects of service quality and trust on loyalty, while commitment shows varied influence. The paper emphasizes the necessity for cooperatives to maintain high service standards and build strong emotional ties with members. This approach is essential for sustaining member engagement and positioning women’s cooperatives as agents of local economic development and female empowerment.